The role of investment to develop regions economically (in Kashkadarya region) - Meylikov Fazliddin Abduhalim ugli (THE INNOVATION ECONOMY, 2026)
This article analyzes the impact of attracting investments on the economic growth in the regions, improvement of living standards, creation of favorable investments, the development of investment activity in our republic, as well as presented statistical data in tables. It also consists of developing proposals and recommendations on determining the role of regional economic development in the development of industrial enterprises, the development of family and small businesses, and the growth of production volumes